Augmented renal clearance in critically ill patients: Incidence, associated factors and effects on vancomycin treatment - Campassi, María Luz (2014)
Objective: An augmented renal clearance has been described in some groups of critically ill patients, and it might induce sub-optimal concentrations of drugs eliminated by glomerular filtration, mainly antibiotics. Studies on its occurrence and determinants are lacking. Our goals were to determine the incidence and associated factors of augmented renal clearance and the efects on vancomycin concentrations and dosing in a series of intensive care unit patients. Methods: We prospectively studied 363 patients admitted during 1 year to a clinical-surgical intensive care unit. Patients with serum creatinine >1.3mg/dL were excluded. Creatinine clearance was calculated from a 24-hour urine collection. Patients were grouped according to the presence of augmented renal clearance (creatinine clearance >120mL/min/1.73m2), and possible risk factors were analyzed with bivariate and logistic regression analysis. In patients treated with vancomycin, dosage and plasma concentrations were registered. Results: Augmented renal clearance was present in 103 patients (28%); they were younger (48±15 versus 65±17 years, p>0.0001), had more frequent obstetric (16 versus 7%, p=0.0006) and trauma admissions (10 versus 3%, p=0.016) and fewer comorbidities. The only independent determinants for the development of augmented renal clearance were age (OR 0.95; p<0.0001; 95%CI 0.93-0.96) and absence of diabetes (OR 0.34; p=0.03; 95%CI 0.12-0.92). Twelve of the 46 patients who received vancomycin had augmented renal clearance and despite higher doses, had lower concentrations. Conclusions: In this cohort of critically ill patients, augmented renal clearance was a common finding. Age and absence of diabetes were the only independent determinants. Therefore, younger and previously healthy patients might require larger vancomycin dosing.